Metric Dimension of Irregular Convex Triangular Networks - S. Prabhu; D. Sagaya Rani Jeba; M. Arulperumjothi; Sandi Klavžar (AKCE International Journal of Graphs and Combinatorics)
Irregular convex triangular networks consist of the interior of a 6-sided convex polygon drawn on the infinite triangular network. Formal description of these applicable networks is provided. In the main result it is proved that the metric dimension of an irregular convex triangular network is either 2 or 3 and the determination of which value is the right one is specified. Metric dimensions of various graph classes and interconnection networks are also collected.